Law Enforcement of Narcotics Crimes Against Children Who Will Be Rehabilitated at the National Narcotics Agency of South Sumatra Province - Hady, Erfan; Zahri, Saipuddin; Mahfuz, Abdul Latif; Sastro, Harmonis (Polteknik Ilmu Pemasyarakatan, 2025)
The abuse of narcotics among children and adolescents has become an increasingly urgent social problem in Indonesia. The harmful effects of narcotics impact not only physical health but also the psychological and social development of children. This study aims to examine the legal protection provided to children involved in narcotics abuse and the role of related institutions in prevention and rehabilitation efforts. The research method used is a normative legal approach combined with library research. This study analyzes regulations related to the juvenile criminal justice system and the role of the National Narcotics Board (BNN) in addressing narcotics issues, including prevention, rehabilitation, and supervision. The results show that despite various laws protecting children, implementation in the field still faces significant challenges, particularly in terms of access to rehabilitation services and public legal awareness. Moreover, BNN’s preventive efforts through education and outreach programs in schools still need strengthening. The implications of this research indicate the need for more intensive collaboration between the government, educational institutions, and the community to enhance prevention efforts and provide more comprehensive support to children who are victims of narcotics abuse.